Digital Teaching Materials Narrative Text-The Fiction of Good Character-Oriented for Class VII MTS/SMP - Ishak Sanusi; Abdur Razak; Mira Nuryanti (PT Inovasi Pratama Internasional, 2024)
The research carried out is a type of development research or Research and Development (R&D). As for the Research and Development (R&D) method in this research, researchers used the ADDIE development model. Data collection techniques used in research are observation, questionnaires, interviews and documentation. The research carried out is a type of development research or Research and Development (R&D). As for the Research and Development (R&D) method in this research, researchers used the ADDIE development model. Data collection techniques used in research are observation, questionnaires, interviews and documentation. The results of research on digital teaching materials for narrative texts - fiction oriented towards noble morals which are arranged in the form of digital flipbook teaching modules, contain linguistic elements, structure, content, inspirational characters and the four characteristics of the apostle (noble character). The implementation of digital teaching materials after going through limited trials and expanding as learning progressed, Indonesian language teachers and students stated that the short story texts containing the four characteristics of the apostle (noble morals) were very suitable and appropriate as teaching material in learning.